The listening renaissance: a theoretical exploration of audio-based digital narratives in literature - Bhuvaneshwari Palanisamy; Rajasekaran V (Humanities & Social Sciences Communications)
Abstract This paper examines the burgeoning phenomenon of audio-based digital narratives and their transformative impact on literature consumption, focusing on the evolving role of listening in the digital age. As audiobooks, podcasts, and other audio formats gain prominence, they challenge traditional notions of reading and storytelling, reshaping individual’s engagement with literary works. Through a theoretical exploration drawing from cognitive theory, media studies, and literary criticism, this study argues that the rise of audio literature represents not merely a shift in medium, but a fundamental change to process and interact with narrative content. The paper investigates the historical evolution of audio narratives, the cognitive processes involved in auditory literary experiences and the emergence of “literary listening” as a distinct skill. It also considers broader implications, including accessibility issues, the democratization of literature, and potential future directions of storytelling in an increasingly audio-centric digital environment. By synthesizing existing research and theoretical frameworks, this study aims to provide a comprehensive understanding of the listening renaissance in literature. The paper concludes by reflecting on the changing nature of literature consumption and the enduring importance of listening in an individual’s engagement with narrative art, suggesting that audio-based digital narratives represent a significant cultural shift associated with literature, rather than just a technological trend.